Supervision of instruction at La Salle Green Hills high school: An assessment - Santos, Celedonia San Luis (Animo Repository, 1986)
This study assesses the program on supervision of instruction at La Salle Green Hills high school with the end view of describing and evaluating the objectives, outcomes and functions of the present supervisory program as implemented by the administrators and academic coordinators. The descriptive method of research was employed to enable the researcher to obtain data on the perceptions of faculty and administrators with regards to the assessment of the program on supervision of instruction at La Salle Green Hills high school. A survey questionnaire, developed by the researcher, was used in obtaining data for the study. In Part I of the questionnaire, the questions were centered on the objectives Part II, on the outcomes as a result of the four dimensions namely, communication, leadership, human relation and staff development and Part III were questions centered on the functions of the supervisory program. The same questionnaire was administered for both faculty and administrators of La Salle Green Hills high school. The respondents were a total of fourteen administrators and sixty eight faculty. The statistical treatment of the data gathered in this research study was furnished by the Statistical Assistance for Research (STAR) in the Computer Center of De La Salle University, Manila under the supervision of Fr. Luke Moortgart. The Mean and Standard Deviation were used to measure the central tendencies and variation of teachers' perception on the implementation of the program on supervision of instruction by the academic coordinators and administrators. One-way analysis of variance (ANOVA) was used to see whether there were differences in the perception of the faculty and the administrators regarding the attainment of the outcomes and the performance of the supervisory functions by the academic coordinators and administrators. The level of significance employed was at .05 level. The following conclusions were drawn from the study: 1. The objectives of the De La Salle Green Hills high school program on supervision of instruction were clear and acceptable to a great extent and attained to a certain extent as perceived by the faculty and administrators. 2. The intended outcomes of the supervisory program were attained to a great extent as perceived by the faculty and administrators. 3. The outcomes of the four dimensions of the supervisory program were attained to a certain extent as perceived by the faculty and attained to a great extent as perceived by the administrators. 4. The academic coordinators and administrators of La Salle Green Hills high school perform their tasks as expected by the faculty to a great extent. 5. There was a significant difference in the perception of teachers and administrators of La Salle Green Hills high school in the attainment of outcomes of the program on supervision and in the performance of the supervisory functions of the administrators. The administrators had higher perceptions of themselves in the attainment of outcomes and in the performance of functions in comparison to the way the faculty perceived them.